PENGUKURAN KINERJA SUMBER DAYA MANUSIA DENGAN MODEL HUMAN RESOURCES SCORECARD PADA PT. XYZ - Ismail; Marwan; Setiawannie, Yuli (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2025)
Data was obtained through brainstorming and interviews with human resource managers, from the interview results obtained the implementation of the company's vision, mission and strategy. Furthermore, questionnaires were distributed to expert respondents, namely human resource managers to obtain priority weights. The KPI design that can be applied by PT. XYZ includes 4 KPIs in the financial perspective, 7 KPIs in the customer perspective, 6 KPIs in the internal and business perspective, and 4 KPIs in the learning and growth perspective. The results of KPI measurements with the traffic light system contain 17 KPIs with a green category indicating that they are in accordance with the company's targets and 4 KPIs with a yellow category indicating that they need to be improved again.